A taxonomic and morphological study of the harmal plant (Peganum harmala) and the extent of the effect of the alcoholic extract of its seeds on the kidney tissue in male albino rabbits in Sunman City (Comprehensive Journal of Science, 2026)
This preliminary study connduted in Libya aimed to investigate the effect of the alcoholic extract of Peganum harmala seeds on the kidney tissue of adult male albino rabbits , the animals were divided into groups and treated with different concentrations of the extract , the results showed highly significant differences between the groups (P